Internalisation and Biological Activity of Nucleic Acids Delivering Cell-Penetrating Peptide Nanoparticles Is Controlled by the Biomolecular Corona - Annely Lorents; Maria Maloverjan; Kärt Padari; Margus Pooga (MDPI AG, 2021)
Nucleic acid molecules can be transferred into cells to alter gene expression and, thus, alleviate certain pathological conditions. Cell-penetrating peptides (CPPs) are vectors that can be used for transfecting nucleic acids as well as many other compounds. CPPs associate nucleic acids non-covalently, forming stable nanoparticles and providing efficient transfection of cells in vitro. However, in vivo, expected efficiency is achieved only in rare cases. One of the reasons for this discrepancy is the formation of protein corona around nanoparticles, once they are exposed to a biological environment, e.g., blood stream. In this study, we compared protein corona of CPP-nucleic acid nanoparticles formed in the presence of bovine, murine and human serum. We used Western blot and mass-spectrometry to identify the major constituents of protein corona forming around nanoparticles, showing that proteins involved in transport, haemostasis and complement system are its major components. We investigated physical features of nanoparticles and measured their biological efficiency in splice-correction assay. We showed that protein corona constituents might alter the fate of nanoparticles in vivo, e.g., by subjecting them to phagocytosis. We demonstrated that composition of protein corona of nanoparticles is species-specific that leads to dissimilar transfection efficiency and should be considered while developing delivery systems for nucleic acids.